2018
DOI: 10.1038/s41598-018-34240-x
|View full text |Cite
|
Sign up to set email alerts
|

Triple herbal extract DA-9805 exerts a neuroprotective effect via amelioration of mitochondrial damage in experimental models of Parkinson’s disease

Abstract: Moutan cortex, Angelica Dahurica root, and Bupleurum root are traditional herbal medicines used in Asian countries to treat various diseases caused by oxidative stress or inflammation. Parkinson’s disease (PD) has been associated with mitochondrial dysfunction, but no effective treatment for mitochondrial dysfunction has yet been identified. In this study we investigated the neuroprotective effects of the triple herbal extract DA-9805 in experimental models of PD. DA-9805 was prepared by extracting three dried… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(10 citation statements)
references
References 51 publications
1
9
0
Order By: Relevance
“…This result demonstrates a similar tendency to that noted in PD patients. However, DA-9805-induced recovery of the motor dysfunctions was only associated with a tendency to increase DA levels, which was particularly similar to the results of a previous study with MPTP-induced PD mice ( Jeong et al, 2018 ). However, striatal Ach showed the strongest correlation with rotarod latency times ( Table 1 and Figure 2B ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…This result demonstrates a similar tendency to that noted in PD patients. However, DA-9805-induced recovery of the motor dysfunctions was only associated with a tendency to increase DA levels, which was particularly similar to the results of a previous study with MPTP-induced PD mice ( Jeong et al, 2018 ). However, striatal Ach showed the strongest correlation with rotarod latency times ( Table 1 and Figure 2B ).…”
Section: Discussionsupporting
confidence: 89%
“…A standardized DA-9805 (batch number: MB1603) was provided from Dong-A ST (Yong-in, South Korea). Condition for extraction and quality control of DA-9805 were described as reported methods previously ( Jeong et al, 2018 ). Briefly, same amounts of MRC, ADR, and BR were extracted at room temperature (20–25°C) for 24 h with 90% ethanol, evaporated and subsequently maintained at 4°C until use.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…(Fu et al, 2015) Herbal extracts like the moutan cortex, Angelica dahurica root, and bupleurum root also exerts neuroprotective action in PD. (Jeong et al, 2018) Many lavonoids are proposed to exhibit neuroprotective actions primarily through anti-oxidant mechanisms. (Magalingam et al, 2015) Apart from these, artemisia (Pal and Ghosh, 2018), isolongifolene (Balakrishnan et al, 2018), and caffeine (Khadrawy et al, 2017) and many other drugs have shown signi icant therapeutic roles in PD.…”
Section: Oxidative Stress Indicatorsmentioning
confidence: 99%
“…CoQ10 and creatine [Figure 1D] combination therapy has been investigated in a MPTP mouse model of PD. [35] The researchers show that supplementation with these combined agents in mice through a diet with 2% creatine and 1% CoQ10 for 1 week before MPTP treatment (40 mg/kg body weight daily for 28 days through osmotic pumps) produced additive neuroprotective effects against dopamine depletion in the striatum and loss of tyrosine hydroxylase (TH) neurons in the SNpc, reduced lipid peroxidation and pathologic SNCA accumulation in SNpc neurons, and loss of DAergic neurons. Resveratrol [Figure 1E] is a well-known antioxidant that exerts extensive pharmacological effects including anti-inflammatory, anti-mutation, anti-tumor, and blood fat regulatory functions.…”
Section: Antioxidant Compounds In Experimental Models Of Pdmentioning
confidence: 99%